Structural bases for a complete myotoxic mechanism: Crystal structures of two non-catalytic phospholipases A(2)-like from Bothrops brazili venom - Fernandes, Carlos A. H. [UNESP]; Comparetti, Edson J. [UNESP]; Borges, Rafael J. [UNESP]; Huancahuire-Vega, Salomon; Ponce-Soto, Luis Alberto; Marangoni, Sergio; Soares, Andreimar M.; Fontes, Marcos R. M. [UNESP] (Elsevier B.V., 2013)
Bothrops brazili is a snake found in the forests of the Amazonian region whose commercial therapeutic antibothropic serum has low efficacy for local myotoxic effects, resulting in an important public health problem in this area. Catalytically inactive phospholipases A(2)-like (Lys49-PLA(2)s) are among the main components from Bothrops genus venoms and are capable of causing drastic myonecrosis. Several studies have shown that the C-terminal region of these toxins, which includes a variable combination of positively charged and hydrophobic residues, is responsible for their activity. In this work we describe the crystal structures of two Lys49-PLA(2)s (BbTX-II and MIX-II) from B. brazili venom and a comprehensive structural comparison with several Lys49-PLA(2)s. Based on these results, two independent sites of interaction were identified between protein and membrane which leads to the proposition of a new myotoxic mechanism for bothropic Lys49-PLA(2)s composed of five different steps. This proposition is able to fully explain the action of these toxins and may be useful to develop efficient inhibitors to complement the conventional antivenom administration. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Phospholipase A(2)-like; Myotoxic mechanism; Snake venom; X-ray crystallography; Lys49-phospholipase A(2); Amazonian snake